Location-semantic-based location privacy protection for road network - Hui CHEN; Xiao-lin QIN (Tongxin xuebao)
Mobile users suffer location privacy leakage threat as enjoy location-based services (LBS).Therefore,it was important to provide effective policy for location privacy protection.Conventional protection approaches were mainly based on spatial cloaking,which leads to the anonymous effectiveness suffer great reduction if the attacker obtains more background knowledge with respect to the cloaking region,especially semantic information of the location.To prevent sensitive location information leakage for the location semantics being analyzed,and consider the characteristic that most users move on road networks,a location-semantic-based location privacy protection method for road networks was pro-posed.The proposed method considers users' personalized privacy requirements well.The feasibility and effectiveness of the proposed method are verified through experiments for many scenarios.